Time or Space? Relative Importance of Geographic Distribution and Interannual Variation in Three Lineages of the Ascidian Pyura chilensis in the Southeast Pacific Coast - Haye, Pilar A.; Turon, Xavier; Segovia, Nicolás I. (Frontiers in Marine Science, 2021)
Spatial and temporal variation of environmental parameters can affect dispersal, recruitment and population persistence of marine benthic species. Studies including inter-annual comparisons of genetic structure often indicate high/moderate temporal heterogeneity in marine invertebrates, which may be a prevailing pattern. This suggests that temporal studies are necessary to understand the dynamics of marine metapopulations. In this study, we analyzed the spatio-temporal genetic structure of the ascidian Pyura chilensis, a low dispersal sessile marine species endemic from the Southeast Pacific coast and highly demanded for human consumption. We sequenced a fragment of the mitochondrial gene Cytochrome Oxidase I (COI) from 1,005 individuals of six locations (30-40 individuals per site and year) spanning a wide latitudinal range (24º to 42ºS) and sampled over five years (2012, 2014, 2015, 2016, 2017). The genetic structure of COI indicates the presence of three monophyletic lineages (haplogroups 1 to 3) previously described for the species, being one of them highly divergent and geographically restricted ( 39ºS, Los Molinos). Considering the whole dataset, a picture of strong spatial differentiation but temporal stability emerged in Pyura chilensis. However, detailed studies of the two main lineages revealed important differences in the extent of spatio-temporal variation. Analyses using haplotype frequencies sorted by site and year showed that, for haplogroup 1, genetic variation was explained mainly by differences between sites, while for haplogroup 2 differences between years were prevailing. Haplogroup 3 was restricted to the most southern sites, and also showed inter-annual variability in its frequency. These results point to disparate patterns of genetic differentiation, which may reflect different adaptive scope or variation in reproductive and dispersal features and could be a response to extreme events such as El Niño (2015-2016). This work calls for caution when obtaining general trends in species clearly differentiated in lineages, and prompts instead for separate analyses of sub-specific genetic lineages whenever possible.